Investment Allowances, Initial Allowances and Cheap Loans as Means of Encouraging Investment - Black, J. (Review of Economic Studies, 1959)
Journal Article Investment Allowances, Initial Allowances and Cheap Loans as Means of Encouraging Investment Get access J. Black J. Black Oxford Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 27, Issue 1, October 1959, Pages 44–49, https://doi.org/10.2307/2296049 Published: 01 October 1959